2017
DOI: 10.1124/jpet.117.244806
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial-Based Therapeutics for the Treatment of Spinal Cord Injury: Mitochondrial Biogenesis as a Potential Pharmacological Target

Abstract: Spinal cord injury (SCI) is characterized by an initial trauma followed by a progressive cascade of damage referred to as secondary injury. A hallmark of secondary injury is vascular disruption leading to vasoconstriction and decreased oxygen delivery, which directly reduces the ability of mitochondria to maintain homeostasis and leads to loss of ATP-dependent cellular functions, calcium overload, excitotoxicity, and oxidative stress, further exacerbating injury. Restoration of mitochondria dysfunction during … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
76
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 96 publications
(78 citation statements)
references
References 181 publications
(193 reference statements)
0
76
0
2
Order By: Relevance
“…Exploring different facets of mitochondrial function should provide new insights as to how mitochondria may hold the key to “cellular memory” long after a stressor is removed or ceases. Clinically, ROS scavengers such as Tempol and the specific mitochondria targeted compound XJB‐5‐131 have shown structural and functional improvements in animal models of spinal cord and traumatic brain injury, Huntington's, aging muscle contractility and others . Moreover, Tempol is safe in humans .…”
Section: Resultsmentioning
confidence: 99%
“…Exploring different facets of mitochondrial function should provide new insights as to how mitochondria may hold the key to “cellular memory” long after a stressor is removed or ceases. Clinically, ROS scavengers such as Tempol and the specific mitochondria targeted compound XJB‐5‐131 have shown structural and functional improvements in animal models of spinal cord and traumatic brain injury, Huntington's, aging muscle contractility and others . Moreover, Tempol is safe in humans .…”
Section: Resultsmentioning
confidence: 99%
“…Many studies have shown that transient ischaemia and hypoxia can cause spinal nerve necrosis . The primary mechanisms whereby this occurs include free radical and lipid peroxidation, intracellular calcium disruption, release of inflammatory factors, excitatory neurotransmitter damage, apoptosis of nerve cells and a series of pathophysiological processes . Continual ischaemia and hypoxia can aggravate SCIRI, resulting in secondary oedema of the spinal cord and increased intrathecal pressure, potentially leading to increased tissue damage and aggravated loss of motor function.…”
Section: Discussionmentioning
confidence: 99%
“…31 The primary mechanisms whereby this occurs include free radical and lipid peroxidation, intracellular calcium disruption, release of inflammatory factors, excitatory neurotransmitter damage, apoptosis of nerve cells and a series of pathophysiological processes. [3][4][5][6] Continual ischaemia and hypoxia can aggravate SCIRI, resulting in secondary oedema of the spinal cord and increased intrathecal pressure, potentially leading to increased tissue damage and aggravated loss of motor function. At F I G U R E 4 Dex pre-treatment effectively attenuates the expression level of CNPY2 and GRP78 mRNA on ER of spinal cord induced by SCIRI.…”
Section: Spinal Cord Ischaemia-reperfusion Injury Can Lead To Dysfuncmentioning
confidence: 99%
See 2 more Smart Citations